Answer :

By splitting the middle


7y2 - 11y/3 - 2/3 = 0


21y2 - 11y - 2 = 0


21y2 + (3y - 14y) - 2 = 0


21y2 + 3y - 14y - 2 = 0


3y (7y + 1) - 2(7y + 1) = 0


(7y + 1)(3y - 2) = 0


y = - 1/7, 2/3


Verification:


Sum of the zeroes = - (coefficient of x) ÷ coefficient of x2


α + β = - b/a


(- 1/7) + (2/3) = - (- 11)/21


= 11/21 = 11/21


Product of the zeroes = constant term ÷ coefficient of x2


α β = c/a


(- 1/7)(2/3) =


- 2/21 = - 2/21


Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses